(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Complementary feeding patterns between 6-23 months are critical for optimal child development and growth. Poor complementary feeding patterns remain a primary cause of malnutrition and childhood mortality in developing countries. This study assessed complementary feeding practices and their determinants among mothers at a tertiary-level hospital. Materials and Method: This is a cross-sectional study conducted among 100 mothers of children aged 6 to 23 months attending the paediatric outpatient department of a tertiary-level hospital. The variables used were age at introduction, food types, frequency of feeds, and variety of diet based on the WHO classification of food groups. Food group intake was estimated by a 24-hour dietary recall. Minimum dietary diversity (MDD) was defined as ≥2 WHO food groups eaten, and minimum meal frequency (MMF) based on age-specific WHO cut-offs. Statistical analysis with descriptive statistics, chi-square tests, Spearman correlation, and multivariable logistic regression was done using SPSS version 26.Results: More than half (72%) had started complementary feeding after 6 months, and 8% had begun complementary feeding before 6 months. Rice foods were the most common complementary foods (khichuri 32%, rice powder 21%). The mean dietary diversity was a mere 1.5 food groups within 24 hours, much lower than the recommended ≥4 groups. Most children had met the minimum meal frequency but not dietary diversity. Maternal education had a marked effect on dietary variety (p=0.037), where educated mothers were more likely to offer diversified foods. The household income also had an impact (p = 0.001), but maternal education had greater correlations. Conclusion: Despite the early initiation of complementary feeding being high, dietary diversity was low. Maternal education was the most significant predictor of adequate feeding practice, and it highlighted the significance of some forms of nutrition counseling interventions. J Med Coll Women Hosp.2026; 22(1): 67-79